ANALYSIS OF CONSUMER LEGAL PROTECTION OVER CONSUMER HOUSE CERTIFICATE GUARANTEE BY DEVELOPER TO BANK IN THE CASE OF PT. ACK - Alicya Rahmawati (Law Research Review Quarterly, 2026)
Problems in the housing sector often position consumers in a weak position, especially in legal relationships involving developers who are in default against banks. This research aims to analyze the legal position of consumers in housing transactions when the consumer's certificate is guaranteed by the developer to the bank and what forms of legal protection efforts exist for consumers. The research method used is normative research with statutory, conceptual and comparative approaches. The research results show that the position of consumers in the Sale and Purchase Agreement is still weak and expectant because the rights owned by consumers are not yet full material rights, so consumers cannot yet be called the holder of ownership rights to the housing unit. Consumers who do not yet hold property rights make consumers vulnerable to developer default or disputes with third parties such as banks as creditors holding mortgage rights. Comprehensive legal protection, both preventive and repressive, is needed, realized through clear regulations, monitoring the implementation of agreements, and effective dispute resolution procedures. This research emphasizes the importance of strengthening the position of consumers in order to realize legal certainty and legal protection for housing consumers.